Gating monolayer and bilayer graphene with a two-dimensional semiconductor - Randy M. Sterbentz; Bogyeom Kim; Anayeli Flores-Garibay; Kristine L. Haley; Nicholas T. Pereira; Kenji Watanabe; Takashi Taniguchi; Joshua O. Island (npj 2D Materials and Applications)
Abstract Metals are commonly used as electrostatic gates in devices due to their abundant charge carrier densities that are necessary for efficient charging and discharging. A semiconducting gate can be beneficial for certain fabrication processes, in low light conditions, and for specific gating properties. We determine the effectiveness and limitations of a semiconducting gate in graphene and bilayer graphene devices. Using the semiconducting transition metal dichalcogenides molybdenum disulfide (MoS2), molybdenum diselenide (MoSe2), tungsten disulfide (WS2), and tungsten diselenide (WSe2), we show that two-dimensional semiconductors can be used to suitably gate the graphene devices under appropriate operating conditions. For single-gated devices, semiconducting gates are comparable to metallic gates below liquid helium temperatures but include resistivity features resulting from gate voltage clamping of the semiconductor. In dual-gated devices, we pin down the parameter range of effective operation and find that the semiconducting depletion regime results in clamping and hysteresis from defect-state charge trapping.